STUDI TEMPERAMEN SAPI BALI BERTANDUK DAN TIDAK BERTANDUK (Study on the Temperament of Polled and Horned Bali Cattle) - Abdul Qayyum; Baco Sudirman; zulkharnaim zulkharnaim (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
This study was aimed to determine the nature of the differences in temperament of horned and polled Bali cattle. The research was conducted in February-March 2018 in Maiwa Ranch/Maiwa Breeding Center (MBC) Enrekang regency. The research used 25 heads of Bali Cattle, 19 heads of horned Bali cattle and 6 heads of Bali polled. Temperament test data was analyzed by descriptive and cortisol levels were analyzed using T-test statistical analysis, temperance, and cortisol level test results. Data were analyzed using covariance analysis. The results of this study indicated that according to the temperament tests parameters (pen score, chute score, chute exit velocity), Bali polled were tamer than Bali horned cattle. Cortisol levels of Bali polled also observed lower than the horned Bali cattle